UNIDADES FRASEOLÓGICAS ESPECIALIZADAS: NOVAS PERSPECTIVAS PARA SUA IDENTIFICAÇÃO E TRATAMENTO - Bevilacqua, Cleci Regina (Organon, 2012)
This paper presents Specialised Phraseologic Units, within the framework of theTerminology’s Communicative Theory (TCT) proposed by Cabré (1998, 1999). First, we will brieflyintroduce the basic theoretic principles of this theory; we will then discuss the implications of theiracceptance for the analysis and treatment of specialised phraseology. Finally, we will mention some ofthe consequences of this new approach for terminological research in the context of Mercosul.